Multimorbidity and catastrophic health expenditure: Evidence from the China Health and Retirement Longitudinal Study - Li, Haofei; Chang, Enxue; Zheng, Wanji; Liu, Bo; Xu, Juan; Gu, Wen; Zhou, Lan; Li, Jinmei; Liu, Chaojie; Yu, Hongjuan; Huang, Weidong (Frontiers in Public Health, 2022)
Background: Population ageing accompanied by multimorbidity imposes a great burden on households and the healthcare system. This study aimed to determine the incidence and determinants of catastrophic health expenditure (CHE) in the households of old people with multimorbidity in China. Methods: Data were obtained from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2018, with 3511 old people (≥60 years) with multimorbidity responding to the survey on behalf of their households. CHE was identified using two thresholds: ≥10% of out-of-pocket (OOP) health spending in total household expenditure (THE) and ≥40% of OOP health spending in household capacity to pay (CTP) measured by non-food household expenditure. Logistic regression models were established to identify the individual and household characteristics associated with CHE incidence. Results: The median values of THE, OOP health spending, and CTP reached 19900, 1500, and 10520 Yuan, respectively. The CHE incidence reached 31.5% using the ≥40% CTP threshold and 45.6% using the ≥10% THE threshold. It increased by the number of chronic conditions reported by the respondents (aOR=1.293-1.855, p<0.05) and decreased with increasing household economic status (aOR=1.622-4.595 relative the highest quartile, p<0.001). Hospital admissions over the past year (aOR=6.707, 95% CI: 5.186 to 8.674) and outpatient visits over the past month (aOR=4.891, 95% CI: 3.822 to 6.259) of the respondents were the strongest predictors of CHE incidence. The respondents who were male (aOR=1.266, 95% CI: 1.054 to 1.521), married (OR=1.502, 95% CI: 1.211 to 1.862), older than 70 years (aOR=1.288-1.458 relative to 60-69 years, p<0.05), completed primary (aOR=1.328 relative to illiterate, 95% CI: 1.079 to 1.635) or secondary school education (aOR=1.305 relative to illiterate, 95% CI: 1.002 to 1.701), lived in a small (≤2 members) household (aOR=2.207, 95% CI: 1.825 to 2.669), and resided in the northeast region (aOR=1.935 relative to eastern, 95% CI: 1.396 to 2.682) were more likely to incur CHE. Conclusion: Multimorbidity is a significant risk of CHE. Household CHE incidence increases with the number of reported chronic conditions. Socioeconomic and regional disparities in CHE incidence persist in China. Keywords：Multimorbidity, Catastrophic health expenditure, Economic burden, Elderly, China